Impact of Organizational Citizenship Behavior on Job Performance in Jordan: The Mediating Role of Perceived Training Opportunities - Albloush, Ahmad; Taha, Sadi; Nassoura, Abdelrahim; Vij, Anu; Prakash Bohra, Om; Masouad, Najeeb; Abu Hussien, Alhareth (International Journal of Psychosocial Rehabilitation, 2020)
This study examined the effect of organizational citizenship behavior (OCB) on the job performance of Greater Amman Municipality (GAM) through the mediating factor of perceived training opportunities (PTO). This study involved data from 344 employees working in 22 regions in GAM. PLS-SEM was applied to test the hypotheses. The validity and reliability of the measurement and the structural models were confirmed. The results showed that OCB positively affects job performance. Findings also showed a partial mediation effect of PTO on the relationship between OCB and job performance. The main practical contribution of the study is providing significant insights to the Jordanian government and GAM to explain a roadmap that helps in understanding the most influential factors on job performance. Based on the findings, the study recommends the GAM should improve employees OCB. Therefore, PTO is enhanced, which leads to a positive and significant impact on job performance.